2021
DOI: 10.1093/brain/awab353
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting stroke-like episodes and outcomes in mitochondrial disease

Abstract: In this retrospective, multicentre, observational cohort study, we sought to determine the clinical, radiological, EEG, genetics and neuropathological characteristics of mitochondrial stroke-like episodes and to identify associated risk predictors. Between January 1998 and June 2018, we identified 111 patients with genetically-determined mitochondrial disease who developed stroke-like episodes. Post-mortem cases of mitochondrial disease (n = 26) were identified from Newcastle Brain Tissue Resource. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 72 publications
0
42
2
Order By: Relevance
“…These findings highlight that methodologically robust clinical trials are imperative to address the remaining uncertainty relating to the treatment of l -arginine in patients with MELAS syndrome. Because stoke-like episodes are increasingly recognized as evolving brain syndromes driven by seizure activity, 1,50 seizure treatments, including infusions of AEDs or use of anesthesia agents, should be prioritized in these patients. While there are potential cultural differences in shared decision-making for medical practice in rare diseases globally, we would encourage mitochondrial experts to share this information about l -arginine with patients and colleagues to allow them to make an informed decision.…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight that methodologically robust clinical trials are imperative to address the remaining uncertainty relating to the treatment of l -arginine in patients with MELAS syndrome. Because stoke-like episodes are increasingly recognized as evolving brain syndromes driven by seizure activity, 1,50 seizure treatments, including infusions of AEDs or use of anesthesia agents, should be prioritized in these patients. While there are potential cultural differences in shared decision-making for medical practice in rare diseases globally, we would encourage mitochondrial experts to share this information about l -arginine with patients and colleagues to allow them to make an informed decision.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Genetics frontiersin.org vascular distribution and demonstrate variable lesion reversibility (Chen et al, 2020;Ng et al, 2021b). A recent study reported mismatched hypometabolism in SLEs (Finsterer et al, 2021), which may be explained by a reduced ability of mitochondria to utilize glucose.…”
Section: Mancuso Et Al (2014) (Continued On Following Page)mentioning
confidence: 99%
“…Nervous system symptoms are the most prominent phenotypes of m.3243A>G. 80% of MELAS syndrome cases are associated with m.3243A>G, and the most common age of onset is 2–40 years, although late-onset cases have been reported ( Ayman W El-Hattab, 2018 ). SLEs are a typical symptom of MELAS syndrome, which shows increased T2-weighted signal areas involving both cortical and subcortical areas on temporal, occipital and parietal lobes that do not correspond to the classic vascular distribution and demonstrate variable lesion reversibility ( Chen et al, 2020 ; Ng et al, 2021b ). A recent study reported mismatched hypometabolism in SLEs ( Finsterer et al, 2021 ), which may be explained by a reduced ability of mitochondria to utilize glucose.…”
Section: Phenotypementioning
confidence: 99%
“…Further, accumulation of ROS and subsequent mitochondrial permeability transition pore (mPTP) opening or activation of Hypoxia Inducible Factor (HIF)-1α pathways trigger apoptosis. Thereby, mPTP opening leads to elevated calcium release and even higher levels of ROS [105][106][107][108][109][110]. Especially high amounts of ROS drive a series of downstream effects and act as central regulator.…”
Section: The Role Of Mitochondria In Cell Death Mechanisms and Reperf...mentioning
confidence: 99%